2010
DOI: 10.1007/s12275-009-0384-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of hemO encoding heme oxygenase in Clostridium perfringens

Abstract: A Gram-positive anaerobic pathogen, Clostridium perfringens, causes clostridial myonecrosis or gas gangrene in humans by producing numerous extracellular toxins and enzymes that act in concert to degrade host tissues. The ability of infectious bacteria to acquire sufficient iron during infection is essential for the pathogen to cause disease. In the C. perfringens strain 13 genome, a heme oxygenase gene homologue (CPE0214, hemO) was found and its role was examined. The purified recombinant HemO protein showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In the presence of heme, hemO is upregulated, but it is downregulated in the presence of iron (39). The factors responsible for the iron-dependent downregulation of hemO have not been identified.…”
Section: Bacterial Heme Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of heme, hemO is upregulated, but it is downregulated in the presence of iron (39). The factors responsible for the iron-dependent downregulation of hemO have not been identified.…”
Section: Bacterial Heme Sensingmentioning
confidence: 99%
“…The factors responsible for the iron-dependent downregulation of hemO have not been identified. The VirSR TCS and the VirRregulated RNA (VR-RNA) contribute to the positive regulation of hemO and other C. perfringens virulence genes; however, the stimulus of VirSR is still unknown (39,65). It is likely that virulence factors are regulated in the presence of host factors, and it is possible that host heme might be such an environmental signal.…”
Section: Bacterial Heme Sensingmentioning
confidence: 99%
“…However, 12 RRs have low similarity to proteins in other clostridia. Two RRs (CLC_0632 and CLC_1105) show homology (38 and 37% protein identity, respectively) to the VirR regulator, which is part of the Clostridium perfringens TCS VirR-VirS involved in the regulation of numerous toxins in this bacterium (Ba-Thein et al, 1996;Cheung et al, 2009;Cheung et al, 2010;Hassan et al, 2010;Ma et al, 2011;Ohtani et al, 2009;Ohtani et al, 2003;Okumura et al, 2008).…”
Section: Two-component Systems Are Involved In the Regulation Of Bontmentioning
confidence: 99%
“…Consequently, organisms have evolved a variety of mechanisms to minimize toxic effects. Whereas some bacteria rely mostly on their oxygenase to degrade excess heme, such as Neisseria gonorrhoeae (Zhu et al , ) or Clostridium perfringens (Hassan et al , ), an alternative strategy can be found in the eukaryotic parasite Plasmodium s pp. which is capable to sequester excess heme in an insoluble substance called hemozoin (Fitch, ; Jani et al , ; Anzaldi and Skaar, ).…”
Section: Introductionmentioning
confidence: 99%